The The Behavior of PPNI Professional Organizations that Fire Their Members Is Seen from the Point of View of Law and Society - Fani Catur Agustin; Novita Anggraheni; Riska Dhivenka Perwita Putri; Yesi Widiastuti; Luizinha da Costa Gutteres; Aris Prio Agus Santoso (Pusat Unggulan IPTEK, Poltekkes Kemenkes Palembang, 2022)
Indonesian National Nurses Association (PPNI) is an organization that houses all nurses in Indonesia. PPNI aims to improve and develop the knowledge, skills of nursing practice, dignity, welfare and ethics of the nursing profession, strengthen unity and empower nurses. This research aims to find out the various community responses regarding PPNI policies in firing its members who are allegedly not in accordance with the Ppni Articles of Association / Household Budget (AD / ART). It happened because the dismissal of PPNI members did not hammer out the correct procedures. This research method uses qualitative methods. Qualitative method is a research method that produces descriptive data in the form of words obtained from the results of surveys addressed to the public to find out various responses about PPNI policies that fire their members by not going through the correct procedures. Based on research, 82.8% of respondents were aware of the policy governing the dismissal of members in AD / ART. While 17.2% were not aware of the policy. 72.4% argued that the PPNI should not dismiss its members disrespectfully, while 27.6% thought the PPNI should dismiss members disrespectfully. 86.2% stated that PPNI has become a good organization while 13.8% do not agree with it. 82.8% did not accept the dismissal of members disrespectfully while 17.2% responded to the statement. 62.1% stated ppni behavior in accordance with AD / ART while 37.9% stated not in accordance with AD / ART. 69% argued that the professional ethics of PPNI organizations are classified as good so far while 31% stated not to be classified as good.